Beyond the Cyst: The Many Contributions of Isadore Tarlov (1905-1977) to Contemporary Neurosurgical Practice. Issue 5 (November 2016) - Kaul, Anand; Manjila, Sunil; Miller, Jonathan P.
Abstract : N/A: Isadore Max Tarlov (1905-1977) is primarily remembered for his 1938 description of the eponymous perineural "Tarlov cyst." However, during his long career as a neurosurgeon and researcher, he was responsible for many other observations and inventions that influenced the development of neurosurgery in the 20th century. While studying at Johns Hopkins Medical School he was acquainted with Walter Dandy, and he became the first resident to study under Wilder Penfield at the newly formed Montreal Neurological Institute. He made many novel observations about peripheral and cranial nerve anatomy, pioneered nerve anastomosis and grafting techniques, and introduced the concept of fibrin glue. He developed an animal model of spinal cord injury and used it to establish for the first time that functional neurological reserve is proportional to rapidity of injury, because gradual onset of compression is better tolerated by neural tissue than acute compression. He was the first to describe the use of the knee-chest position for lumbar spine surgery to minimize increases in epidural venous pressure due to abdominal compression. Finally, near the end of his career, he published a collection of thoughtful, philosophical essays entitled The Principle of Parsimony in Medicine and Other Essays, in which he advocated for a humanistic and restrained approach to medical practice. In this article, we discuss the contributions of Tarlov to the field of neurosurgery, including many of his lesser-known accomplishments that have become part of neurosurgery's collective legacy.